Expert involvement in science development: (re-)evaluation of an early screening tool for carbon storage site characterization. (June 2015) - Scheer, D.; Konrad, W.; Class, H.; Kissinger, A.; Knopf, S.; Noack, V.
Highlights: Early expert involvement in science development using a Group Delphi approach. Evaluation of the gravitational number (Gr) approach, a screening tool for carbon storage site characterization. Expert assessment indicate good understanding but modest significance of Gr. Oversimplification seems to be the overarching downside aspect of the method. Experts recommend not using the Gr results as a sole basis for decision-making. Abstract: Carbon capture and storage (CCS) science development takes place in a highly contested and politicised environment and cannot be seen isolated from the public debate on energy policies. Early expert and decision-maker involvement in CCS science development thus is necessary for assessing the accountability and reliability of scientific methods and decision-tools. Relying on a participatory Group Delphi exercise with 14 experts involved, we carried out early expert involvement in science development with the evaluation of the so-called gravitational number (Gr) approach – an early screening tool for carbon storage site characterization. The aim was to elicit expert evaluations and judgments on the Gr approach and feeding back these judgments to method developers. Experts hinted to several Gr constraints, specifications and recommendations that served the method developers for re-designing and re-evaluating the screening tool. The expert assessment indicate an overall good understanding of the Gr approach with all but two items (far) beyond the scale midpoint of 3.5 on a seven point Likert scale. Evaluating reservoir characterization criteria, experts ranked safety related criteria more important than capacity related criteria. In a final evaluation of the Gr method, experts agreed unanimously to a very high degree that the Gr number approach alone is not meaningful and a review of Gr results by earth scientist is necessary. Oversimplification, therefore, seems to be the overarching downside aspect of the method that leads to the conclusion not to use the Gr results as a sole basis for decision making on site selection.